54 Suicide prevention among adolescents and young adults. (1st September 2016) - Partonen, Timo
Abstract : Background: In Finland the suicide mortality has decreased by 51% from 1990 to 2014 (from 30.0 to 14.6 per 100, 000). However, within Finland, there are still disparities in the distribution of deaths from suicide by age, gender and region. Current activities for suicide prevention among children, adolescents and young adults are, e.g., KiVa school which includes about 90% of all comprehensive schools in Finland and targets against bullying, Good Hunting Mate! which provides psychosocial support targeted at members of hunting clubs, and Time Out! which provides psychosocial support targeted at men exempted from military or civil service. In addition, the Current Care Guidelines by the Finnish Medical Society DUODECIM which in 2013–2015 have been published for bipolar disorder, borderline personality disorder, depression, eating disorders, insomnia, post-traumatic stress disorder, and schizophrenia support these activities. Further support has been provided by EUGENAS which exchanged the best practices for suicide prevention in 2012–2014 and produced the general and school-based guidelines, and the toolkits for the workplace and for media professionals. The aim of this workshop is to meet and have discussion on problems and suicide prevention measures which target at adolescents and young adults. The most effective interventions to reduce deaths from suicide are also to be discussed.